The role of local products in education and the Erasmus+ program - Kajati György; Németh Mercédesz („RIK-U” Kft., 2020)
Abstract. In this study we present the results of a six-year-long (2014–2019) examination and observation of the role of local products in the European Union’s Erasmus+ youth mobility programs and among young people. In the city of Eger, seven foundations and associations organise Erasmus+ programs, where local products appear as an important part of the education, shaping attitudes and environmental awareness.
https://kmf.uz.ua/wp-content/uploads/2020/09/final_2_kotet-foldrajzfkonf-2020-07-14.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008123
Keywords: local products; Erasmus+; youth exchange; education; non-formal learning